After secular law - Sullivan, Winnifred Fallers, 1950-; Yelle, Robert A.; Taussig-Rubbo, Mateo, 1972- (Stanford, California : Stanford University Press, 2011)
Recent scholarship has called into question the simplistic narrative of a separation between law and religion and blurred the boundaries between these two categories, enabling new accounts of their relation that do not necessarily either collapse them together or return law to a religious foundation. This book gives special attention to the secularism of law, exploring how law became secular, the phenomenology of the legal secular, and the challenges that lingering religious formations and other aspects of globalization pose for modern law's self-understanding.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Religion and law; Religious law and legislation; Secularism; Religion; Religion & beliefs; Philosophy of religion; Religion & politics; Methods, theory & philosophy of law